KARAKTERISASI AROMA DAN RASA BEBERAPA VARIETAS BERAS LOKAL MELALUI QUANTITATIVE DESCRIPTIVE ANALYSIS METHOD - Rakhmi, Ami Teja (Informatika Pertanian, 2013)
Improvement of the national rice production could be done by using superior variety (VUB), which has early age ofmaturity and high productivity. However, the farmers, until now, still fanatics to grow the local rice. The utilization oflocal varieties as genetic resources for producing new superior varieties is expected to be solution. The study used sevenlocal rice varieties (Anak Daro, Si Buyung, Cicih Merah, Mentik Wangi, Bengawan Solo, Rojolele, and Mandoti), to testthe aroma and taste. Quantitative Descriptive Analysis (QDA) using trained panelists was applied. Data obtained wereanalyzed by Multivariate Analysis of Principle Component Analysis technique. Results showed that Mandoti and Rojolelehave similar aroma and characterized by pandan, cereals, buttery, and green aroma. Cicih Merah characterized by creamyand sweet aroma. Mentik Wangi, Bengawan solo, and Anak Daro have similar properties but are not characterized by adistinctive aroma. Flavors of Cicih Merah and Bengawan solo are in one group and characterized by a taste of sweet andumami. Mandoti are in different groups and characterized by a taste of salty and bitter. Mentik Wangi and Si Buyung,Anak Daro and Rojolele even be in one group but not characterized by a distinctive flavor attributes.